2018
DOI: 10.1177/2058738418783404
|View full text |Cite
|
Sign up to set email alerts
|

An inhibitor of spleen tyrosine kinase suppresses experimental crescentic glomerulonephritis

Abstract: Non-selective inhibitors of spleen tyrosine kinase (SYK) efficiently suppress disease in T cell-dependent models of crescentic glomerulonephritis. However, the therapeutic potential of selective SYK inhibitors in this disease has not been established. In addition, we lack knowledge regarding SYK expression in non-myeloid cells in glomerulonephritis. We addressed these two issues in a rat model of nephrotoxic serum nephritis (NTN) using a SYK inhibitor, GS-492429. Disease was induced in Sprague-Dawley rats (Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…A specific contribution of SYK to neutrophil-and monocyte-mediated glomerular inflammation, however, is suggested by studies in SYKdeficient mice and with alternative pharmacologic inhibitors. 16,34,35 In this study, we have confirmed our previous findings, and those of other groups, that SYK expression is upregulated, and that SYK is activated, at sites of glomerular inflammation in renal AAV. 13,16 Our additional in vivo data provide further evidence that SYK contributes to disease pathogenesis, and that clinical studies of SYK inhibition should be considered.…”
Section: Discussionsupporting
confidence: 91%
“…A specific contribution of SYK to neutrophil-and monocyte-mediated glomerular inflammation, however, is suggested by studies in SYKdeficient mice and with alternative pharmacologic inhibitors. 16,34,35 In this study, we have confirmed our previous findings, and those of other groups, that SYK expression is upregulated, and that SYK is activated, at sites of glomerular inflammation in renal AAV. 13,16 Our additional in vivo data provide further evidence that SYK contributes to disease pathogenesis, and that clinical studies of SYK inhibition should be considered.…”
Section: Discussionsupporting
confidence: 91%
“…HIS48-positive neutrophils in the glomeruli, and CD4+ cells within glomeruli, were counted in an average of 25 glomeruli in each kidney sample and expressed as the average number of cells per glomerulus. RECA-1 staining of capillaries in the glomerular tuft was scored as previously described [ 22 ] as follows: 0, normal density of capillaries; 1+, reduced capillary density in <25% of tuft; 2+, reduced capillary density in 25–50% of the tuft; and 3+, reduced capillary density in >50% of the tuft.…”
Section: Methodsmentioning
confidence: 99%